2014
DOI: 10.1007/s00299-014-1657-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant chitinase responses to different metal-type stresses reveal specificity

Abstract: Chitinases in Glycine max roots specifically respond to different metal types and reveal a polymorphism that coincides with sensitivity to metal toxicity. Plants evolved various defense mechanisms to cope with metal toxicity. Chitinases (EC 3.2.1.14), belonging to so-called pathogenesis-related proteins, act as possible second line defense compounds in plants exposed to metals. In this work their activity was studied and compared in two selected soybean (Glycine max L.) cultivars, the metal-tolerant cv. Cherny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…Quite fittingly, we also observed that chitinases were increased in roots of both treatments. These, fungal and bacterial cell wall degenerating enzymes, are thought to be induced during HM stress by changes in cellular oxidative status (Javed et al, 2013) as they contribute to water retention, decrease cell wall elasticity and permeability for metals (Kasprzewska, 2003; Mészáros et al, 2014). However, in addition, we found another cell wall associated enzyme, a ß-expansin (I1MV71) to be highly responsive to tungsten.…”
Section: Discussionmentioning
confidence: 99%
“…Quite fittingly, we also observed that chitinases were increased in roots of both treatments. These, fungal and bacterial cell wall degenerating enzymes, are thought to be induced during HM stress by changes in cellular oxidative status (Javed et al, 2013) as they contribute to water retention, decrease cell wall elasticity and permeability for metals (Kasprzewska, 2003; Mészáros et al, 2014). However, in addition, we found another cell wall associated enzyme, a ß-expansin (I1MV71) to be highly responsive to tungsten.…”
Section: Discussionmentioning
confidence: 99%
“…; Mészáros et al . ). In general, chitinases are ROS‐regulated and thus the reported increased abundance of chitinases is not specific to Cd and rather reflects the general stress response of M. sativa (Metwally et al .…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, they might provide advantages for plants during heavy metal stress. Similarly, Meszaros 26 and Bekesiova 23 found that heavy metal stress could induce more chitinases in plants. Dana et al reported overexpressing chitinases tobacco showed exhibit enhanced levels of resistance to biotic and abiotic stress 27 .…”
Section: Discussionmentioning
confidence: 88%